L-carnitine ameliorated fasting-induced fatigue, hunger, and metabolic abnormalities in patients with metabolic syndrome: a randomized controlled study - Zhang, Jun-jie (Nutr J, 2014)
BACKGROUND: The present study aimed to determine that whether L-carnitine infusion could ameliorate fasting-induced adverse effects and improve outcomes. METHOD: In this 7-day, randomized, single-blind, placebo-controlled, pilot study, 15 metabolic syndrome (MetS) patients (11/4 F/M; age 46.9 ± 9.14 years; body mass index [BMI] 28.2 ± 1.8 kg/m(2)) were in the L-carnitine group (LC) and 15 (10/5 F/M; age 46.8 ± 10.9 years; BMI 27.1 ± 2.3 kg/m(2)) were in the control group (CT). All participants underwent a 5-day modified fasting therapy introduced with 2-day moderate calorie restriction. Patients in the LC group received 4 g/day of intravenous L-carnitine, while patients in the CT group were injected with saline. Blood pressure (BP), anthropometric characteristics, markers of liver function, metabolic indices (plasma glucose, lipid profiles, uric acid, free fatty acid and insulin) and hypersensitivity C-reactive protein were measured. Perceived hunger was recorded daily by self-rating visual analogue scales. Fatigue was evaluated by Wessely and Powell scores. RESULTS: In contrast to the CT group, total cholesterol, alanine aminotransferase, systolic and diastolic BP did not change significantly in the LC group after prolonged fasting. There were significant differences in weight loss (LC −4.6 ± 0.9 vs. CT −3.2 ± 1.1 kg, P = 0.03), and waist circumference (LC −5.0 ± 2.2 vs. CT −1.7 ± 1.16 cm, P < 0.001), waist hip ratio (LC −0.023 ± 0.017 vs. CT 0.012 ± 0.01, P < 0.001), insulin concentration (LC −9.9 ± 3.58 vs. CT −6.32 ± 3.44 µU/mL, P = 0.046), and γ-glutamyltransferase concentration (LC −7.07 ± 6.82 vs. CT −2.07 ± 4.18, P = 0.024). Perceived hunger scores were significantly increased (P < 0.05) in the CT group during starvation, which was alleviated with L-carnitine administration in the LC group. Physical fatigue (LC −3.2 ± 3.17 vs. CT 1.8 ± 2.04, P < 0.001) and fatigue severity (LC −11.6 ± 8.38 vs. CT 8.18 ± 7.32, P < 0.001) were significantly reduced in the LC group but were aggravated in the CT group. CONCLUSION: Intravenous L-carnitine can ameliorate fasting-induced hunger, fatigue, cholesterol abnormalities and hepatic metabolic changes and facilitate fasting-induced weight loss in MetS patients. TRIAL REGISTRATION: ChiCTR-TNRC-12002835.